2003
DOI: 10.3109/09638280902943223
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating the prosthetic: Traumatic, limb-loss, rehabilitation and refigured military bodies

Abstract: In this article, I look at the role that context of injury plays in the rehabilitation of military patients who sustained a limb amputation as a result of blast injury trauma in Afghanistan and Iraq. This article contrasts the technologically driven model of rehabilitation produced by the US Armed Forces Amputee Patient Care Program at Walter Reed Army Medical Center with a person centered approach building on work in medical anthropology. In this article, two case studies are contrasted illustrating the reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The same man is, Messinger pointed out, considered a failed case if he does not use his prosthetic limb to its potential, even though he has been able to move on in other areas of his life. This kind of research demonstrates the way in which ''individual experiences with suffering and affliction both complement and confound medical practices'' (Messinger 2009b(Messinger :2130 and explores the sometimes profoundly different perspectives of the clinician and patient (DelVecchio- Good 2007).…”
Section: The Practice Of Normality and Normativitymentioning
confidence: 99%
“…The same man is, Messinger pointed out, considered a failed case if he does not use his prosthetic limb to its potential, even though he has been able to move on in other areas of his life. This kind of research demonstrates the way in which ''individual experiences with suffering and affliction both complement and confound medical practices'' (Messinger 2009b(Messinger :2130 and explores the sometimes profoundly different perspectives of the clinician and patient (DelVecchio- Good 2007).…”
Section: The Practice Of Normality and Normativitymentioning
confidence: 99%
“…For example, limb loss occurring as a result of trauma [7], diabetes [8], osteosarcoma [9], vascular diseases [10] and the effects of aging [11] is a major injury that currently affects nearly 20,00,000 people in the USA. Such conditions are often treated by intra-osseous transcutaneous implantable devices that penetrate through the depth of the skin and provide support to the natural tissue to maintain normal function [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…I suggest two possible reasons for their sometimes reluctant but continued participation in the process: first, the medical staff represent the professional authorities, accredited as having the knowledge and expertise to treat these conditions; second, patients share the medical staff's ideas of the (ab)normal body and its treatment in western society. Prosthetics are not, however, a given even though they have been taken for granted in anthropological studies of amputation (see Messinger's (2009) work in the USA and Manderson and Warren and (2010;Warren and Manderson, 2008) work in Australia). Research has shown that patients coming from non-western cultural backgrounds often resist this kind of treatment.…”
Section: Discussionmentioning
confidence: 96%